Optimizing direct power control of DFIG-based WECS using super-twisting algorithm under real wind profile - Hadoune, Aziz; Mouradi, Abderrahman; Mimet, Abdelaziz; Chojaa, Hamid; Dardabi, Chaimae; Gulzar, Muhammad Majid; Alqahtani, Mohammed; Khalid, Muhammad (Frontiers in Energy Research, 2023)
The present study provides an optimization of the direct power control of the doubly fed induction generator used in a wind conversion system as new control approach under an actual wind condition. The aim of this control methodology is to improve the dynamic response of the Wind Energy Conversion System and reduce the impact of wind fluctuations on power generation. By utilizing the STA-based control strategy, the WECS achieves effective regulation of both reactive and active power output. To evaluate its efficacy, comprehensive simulations are conducted using a detailed model of the WECS and an actual wind profile. The obtained results demonstrate that the adopted control strategy successfully tracks the desired power set-point and mitigates the effects of wind power fluctuations and uncertainties on the WECS's power output. Additionally, a comparison is made between the performance of the STA-based control strategy and a conventional approach employing a switching table and hysteresis controller. In terms of handling transients and rejecting disturbances, the STA-based control strategy demonstrates superior performance, showcasing its effectiveness and potential for practical applications.